Influence of race and geographic setting on the management of gastric adenocarcinoma. Issue 2 (18th May 2019) - Ulanja, Mark B.; Beutler, Bryce D.; Rishi, Mohit; Konam, Kenneth G.; Zell, Steven C.; Patterson, Darryll R.; Ambika, Santhosh; Gullapalli, Nageshwara
Abstract: Background and Objectives: Conflicting evidence indicates that both race and geographic setting may influence the management of malignancies such as gastric adenocarcinoma (GAC). Methods: We designed a retrospective cohort study utilizing data from the Surveillance, Epidemiology, and End Results program to identify patients with resectable GAC (N = 15 991). Exposures of interest were race and geographic region of diagnosis (West [WE], Midwest [MW], South [SO], or Northeast [NE]). Endpoints included: (1) recommendation against surgery and (2) gastric adenocarcinoma‐specific survival (GACSS). Multivariable logistic and Cox regression models were used to identify pertinent associations. Results: A total of 15 991 patients were included (2007‐2015). In adjusted analysis, African American individuals more frequently received a recommendation against surgical resection than White (adjusted odds ratio [aOR] = 0.86; 95% confidence interval [CI], 0.76‐0.98), Asian American (aOR = 0.55; 95% CI, 0.46‐0.65), and American Indian (aOR = 0.50; 95% CI, 0.31‐0.82) individuals. In addition to race‐based discrepancies, there was a significant association between geography and management: individuals diagnosed with GAC in the SO were more likely to receive a recommendation against surgery (odds ratio = 1.35; 95% CI, 1.23‐1.49) and exhibited poorer GACSS as compared with those in the WE, MW, or NE regions. Conclusions: Race and geographic region of diagnosis affect treatment recommendations and GACSS among individuals with resectable tumors. African Americans with resectable cancers are more likely to receive a recommendation against surgery than individuals of other racial groups.